Subcutaneous administration of a neutralizing IL‐1β antibody prolongs limb allograft survival. Issue 8 (7th May 2018) - Hautz, Theresa; Grahammer, Johanna; Moser, Dominik; Eberhart, Nadine; Zelger, Bettina; Zelger, Bernhard; Blumer, Michael J.; Drasche, Astrid; Wolfram, Dolores; Troppmair, Jakob; Öfner, Dietmar; Schneeberger, Stefan
Abstract : Cytokine‐expression profiles revealed IL‐1ß highly upregulated in rejecting skin of limb allografts. We investigate the effect of intragraft treatment with a neutralizing IL‐1β antibody in limb transplantation. Following allogenic hind‐limb transplantation, Lewis rats were either left untreated1 or treated with anti‐lymphocyte serum + tacrolimus (baseline)2 ; baseline immunosuppression + anti‐IL‐1β (1 mg/kg once/week, 6‐8 subcutaneous injections) into the transplanted3 or contralateral4 limb. Endpoint was rejection grade III or day 100. Graft rejection was assessed by histology, immunohistochemistry, flow cytometry phenotyping of immune cells, and monitoring cytokine expression. Anti‐IL‐1β injections into the allograft or contralateral limb resulted in a significant delay of rejection onset (controls: 58.60 ± 0.60; group 3: 75.80 ± 10.87, P  = .044; group 4: 73.00 ± 6.49, P  = .008) and prolongation of graft survival (controls: 64.60 ± 0.87; group 3: 86.60 ± 5.33, P  = .002; group 4: 93.20 ± 3.82, P  = .002), compared to controls. Although the phenotype of the graft infiltrating immune cells did not differ between groups, significantly decreased skin protein levels of IL‐1β, IL‐4, IL‐13, IP‐10, MCP‐1, and MCP‐3 in long‐term‐survivors indicate an overall decrease of chemoattraction and infiltration of immune cells as the immunosuppressive mechanism of anti‐IL‐1β. Inhibition of IL‐1β with short‐term systemic immunosuppression prolongs limb allograft survival and represents a promising target for immunosuppression in extremity transplantation. Abstract : Subcutaneous administration of a neutralizing IL‐1b antibody together with short‐term systemic immunosuppression prolongs allograft survival in a rat hind‐limb transplant model by decreasing overall immune cell infiltration in the skin.